Sarcopenia defined by multidimensional factors and its prognostic role in heart failure: a systematic review and meta-analysis - Jinmei Lu; Yi Gao; Lingbo Zhou; Xinhui Peng; Haiming Feng; Zaixing Zheng (Frontiers in Medicine)
ObjectiveTo perform a systematic review and meta-analysis evaluating the impact of sarcopenia—defined by reductions in muscle mass, strength, and/or function—on clinical outcomes in patients with heart failure (HF), thereby informing more effective management strategies.MethodsA comprehensive literature search was conducted through 14 February 2025, using PubMed, Embase, Cochrane Library, and CNKI to identify prospective and retrospective cohort studies involving HF patients diagnosed with sarcopenia based on Asian Working Group for Sarcopenia (AWGS), European Working Group on Sarcopenia in Older People (EWGSOP2), or Ishii criteria. Data extraction was performed using standardized forms, and study quality was assessed using the Newcastle–Ottawa Scale (NOS). Meta-analytical procedures, including heterogeneity assessment and subgroup analyses, were carried out in Stata 18.0 and R 4.4.2.ResultsFifteen studies comprising 5,713 HF patients were included. Pooled analysis demonstrated that sarcopenia significantly increased the risk of adverse clinical outcomes [hazard ratio (HR) = 1.62, 95% confidence interval (CI): 1.35–1.89], including all-cause mortality (HR = 1.89, 95% CI: 1.63–2.15) and major adverse cardiovascular events (HR = 1.37, 95% CI: 1.11–1.64). Subgroup analyses revealed that sarcopenia defined by AWGS criteria and the Ishii score was significantly associated with worse outcomes (HR = 1.63, 95% CI: 1.33–1.94; HR = 1.78, 95% CI: 1.29–2.27, respectively), whereas definitions based on EWGSOP2 did not reach statistical significance (HR = 1.87, 95% CI: 0.70–3.05). Sarcopenia identified through DXA or BIA-based muscle mass assessments was also significantly correlated with adverse outcomes (DXA: HR = 1.53, 95% CI: 1.29–1.78; BIA: HR = 1.85, 95% CI: 1.10–2.61). Statistically significant associations were observed across all remaining subgroups.ConclusionSarcopenia, when defined using multidimensional criteria, is significantly associated with poor clinical outcomes in patients with HF. These findings underscore the importance of implementing comprehensive sarcopenia assessments to enhance prognostic evaluation and guide early intervention. Clinically, adopting multidimensional diagnostic approaches can improve risk stratification and optimize the management of HF patients.Systematic review registrationhttps://inplasy.com/inplasy-2025-3-0023/, identifier INPLASY202530023.